Epidemiology of shoulder and elbow pain in youth baseball players. Issue 2 (2nd April 2016) - Matsuura, Tetsuya; Suzue, Naoto; Iwame, Toshiyuki; Arisawa, Kokichi; Fukuta, Shoji; Sairyo, Koichi
ABSTRACT: Objectives: There are relatively few published epidemiological studies examining the differences in the risk of shoulder and elbow pain in young baseball players. The purpose of this study was to investigate risk factors for shoulder and elbow pain in child and adolescent baseball players. Methods: A total of 1563 players aged 7 to 12 years participated in this investigation. Subjects were asked whether they had experienced episodes of shoulder or elbow pain. We investigated the following risk factors for shoulder and elbow pain: age, position, years of baseball experience, and training hours per week. Data from the groups with and without shoulder and elbow pain were analyzed using multivariate logistic regression models. Results: Among the 1563 participants, 15.9% and 29.2% reported episodes of shoulder and elbow pain, respectively. Multivariate analysis showed that shoulder pain was associated with age 10, 11, and 12 years, and that elbow pain was associated with age 10, 11, and 12 years, playing catcher, and >2 years of baseball experience. Training hours per week were not associated with either shoulder or elbow pain. Conclusion: In over 1000 baseball players aged 7 to 12 years, 15.9% reported episodes of shoulder pain, while 29.2% reported elbow pain in the throwing arm. The associated risk factors were different for each type of pain. Shoulder pain was associated with increased age while elbow pain was associated with increased age, increased years of baseball experience, and playing catcher.